1999
DOI: 10.1135/cccc19990895
|View full text |Cite
|
Sign up to set email alerts
|

Four Decades of Organic Chemistry of closo-Boranes: A Synthetic Toolbox for Constructing Liquid Crystal Materials. A Review

Abstract: Introduction and transformations of organic functional groups to ten- and twelve-vertex closo-boranes and heteroboranes is reviewed in the context of preparation of liquid crystalline compounds. The review, containing 198 references, is designed as a synthetic manual for materials chemists and focuses on methods for engineering molecules with elongated shapes and variable dipole moments. Several underdeveloped aspects of closo-borane chemistry are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 136 publications
(293 reference statements)
0
48
0
1
Order By: Relevance
“…[21] Its derivatives have emerged as widely used starting materials for the preparation of boron-rich compounds. [6,8,22] They have been applied for the preparation of ionic liquids with [R 3 N-closo-B 12 H 11 ] À ions (R = alkyl), [23] as building blocks in ionomers, [24] for compounds with nonlinear optical (NLO) properties, [25] as weakly coordinating anions [R 3 N-closo-B 12 F 11 ] À (R = H, alkyl), [26] as ligands in transition-metal chemistry, for example in [RuCOA C H T U N G T R E N N U N G (PPh 3 ) 2 (H 2 N-closo-B 12 H 11 )], [27] and for pharmaceuticals, [6,28] for example, for boron neutron capture therapy (BNCT). [29] Exhaustive treatment of [closo-B 12 H 12 ] 2À with H 2 NSO 3 H resulted in double substitution giving (H 3 N) 2 -closo-B 12 H 10 .…”
Section: Salts Of the [1-h 2 N-closo-cb 11 H 11 ]mentioning
confidence: 98%
See 2 more Smart Citations
“…[21] Its derivatives have emerged as widely used starting materials for the preparation of boron-rich compounds. [6,8,22] They have been applied for the preparation of ionic liquids with [R 3 N-closo-B 12 H 11 ] À ions (R = alkyl), [23] as building blocks in ionomers, [24] for compounds with nonlinear optical (NLO) properties, [25] as weakly coordinating anions [R 3 N-closo-B 12 F 11 ] À (R = H, alkyl), [26] as ligands in transition-metal chemistry, for example in [RuCOA C H T U N G T R E N N U N G (PPh 3 ) 2 (H 2 N-closo-B 12 H 11 )], [27] and for pharmaceuticals, [6,28] for example, for boron neutron capture therapy (BNCT). [29] Exhaustive treatment of [closo-B 12 H 12 ] 2À with H 2 NSO 3 H resulted in double substitution giving (H 3 N) 2 -closo-B 12 H 10 .…”
Section: Salts Of the [1-h 2 N-closo-cb 11 H 11 ]mentioning
confidence: 98%
“…[21,30,31] Similar to the chemistry of closo-dodecaborates carrying amino or ammonio substituents and in contrast to the chemistry of aminocarba-closo-dodecacarborates, the syntheses and reactions of the isoelectronic amino-substituted dicarba-closo-dodecaboranes, which have the R 2 N group attached either to boron or carbon, are well studied. [8,32,33] Their investigation dates back to the 1960s with the preparation of 1-H 2 N-1,2-closo-C 2 B 10 H 11 , [34] 3-Et 2 N-1,2-closo-C 2 B 10 H 11 , [35] and 3-H 2 N-1,2-closo-C 2 B 10 H 11 . [36] Carboranes containing two amino groups are far less studied and only 1,7-(H 2 N) 2--1,7-closo-C 2 B 10 H 10 and 1,12-(H 2 N) 2 -1,12-closo-C 2 B 10 H 10 were described, whereas the 1,2-isomer was reported to be less stable.…”
Section: Salts Of the [1-h 2 N-closo-cb 11 H 11 ]mentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Although some products were generated by carbon extrusion, no [1-closo-CB 9 H 10 ] À derivatives were found. In order to generate the latter, a regioselective cluster deboronation on E was of utmost importance, and we found K[NC 4 À , application of 11 B NMR rules [18] for closo species, and the position of the singlet at d = À16.2 ppm indicated that a regioselective alkyl substitution at the 6-position in [1-closo-CB 9 H 10 ] À had taken place from the readily available 1,2-closo-C 2 B 10 H 12 neutral compounds. The assignments indicated on the 11 B{ 1 H}-11 B{ 1 H} 2D COSY NMR spectrum in Figure 1 are consistent with the structure of [6-Me-1-closo-CB 9 H 9 ] À : B10 is correlated with B6, B{7,9}, and B8; B8 is correlated with B10, B{7,9}, and B{4,5}; B{7,9} is correlated with B10, B8, B6, B{4,5}, and B{2,3}.…”
Section: Dedicated To Dr Raikko Kivekäs On the Occasion Of His 60th mentioning
confidence: 99%
“…[3,4] This has stimulated the search for new methods of synthesis; [1-closo-CB 9 H 10 ] À was originally obtained from B 10 H 14 and CN À but is now more conveniently produced from [6-(NMe 3 )-nido-6-CB 9 H 11 ] by dehydrogenation.…”
Section: Dedicated To Dr Raikko Kivekäs On the Occasion Of His 60th mentioning
confidence: 99%